Reliability of intra‐oral quantitative sensory testing (QST) in patients with atypical odontalgia and healthy controls – a multicentre study. (6th October 2014) - Baad‐Hansen, L.; Pigg, M.; Yang, G.; List, T.; Svensson, P.; Drangsholt, M.
Summary The reliability of comprehensive intra‐oral quantitative sensory testing (QST) protocol has not been examined systematically in patients with chronic oro‐facial pain. The aim of the present multicentre study was to examine test–retest and interexaminer reliability of intra‐oral QST measures in terms of absolute values and z‐scores as well as within‐session coefficients of variation (CV) values in patients with atypical odontalgia (AO) and healthy pain‐free controls. Forty‐five patients with AO and 68 healthy controls were subjected to bilateral intra‐oral gingival QST and unilateral extratrigeminal QST (thenar) on three occasions (twice on 1 day by two different examiners and once approximately 1 week later by one of the examiners). Intra‐class correlation coefficients and kappa values for interexaminer and test–retest reliability were computed. Most of the standardised intra‐oral QST measures showed fair to excellent interexaminer (9–12 of 13 measures) and test–retest (7–11 of 13 measures) reliability. Furthermore, no robust differences in reliability measures or within‐session variability (CV) were detected between patients with AO and the healthy reference group. These reliability results in chronic orofacial pain patients support earlier suggestions based on data from healthy subjects that intra‐oral QST is sufficiently reliable for use as a part of a comprehensive evaluation of patients with somatosensory disturbances or neuropathic pain in the trigeminal region.